BUKU Ajar ilmu kesehatan telinga-hidung tenggorok kepala leher editor, H Afianty Arsyad Soepardi, H. Nurbaiti Iskandar - Iskandar, H. Nurbaiti; Supardi, H. Efianty Arsyad (2004)
xiii, 260 hlm ilus 26 cm